Application of Set Covering Location Problem for Organizing the Public Postal Network - Šarac, Dragana; Kopić, Miloš; Mostarac, Katarina; Kujačić, Momčilo; Jovanović, Bojan (Promet - Traffic&Transportation, 2016)
Most countries of the European Union ensure certain obligations (criteria) which universal service providers must meet to ensure the realization of the universal service. These criteria vary from country to country, giving their own choice of an optimal model for the density of the postal network. Such postal network of the operator providing universal postal service must be organized so that post offices are accessible at the optimal distance from the user. This paper presents two different approaches. The first one is based on the population criteria determined in the previous study. The second one is new, a general method created to determine the minimum number of postal unit applications of Set Covering Location Problem. The authors apply both methods on real data collected from the Serbian municipalities and finally, compare the obtained results.